Modulating zymogen granule formation in pancreatic AR42J cells - Rinn, Cornelia; Prüssing, Judith (Experimental cell research, 2012)
Zymogen granules (ZG) are specialized organelles in the exocrine pancreas which allow digestive enzyme storage and regulated secretion. To investigate ZG biogenesis, cargo sorting and packaging, suitable cellular model systems are required. Here, we demonstrate that granule formation in pancreatic AR42J cells, an acinar model system, can be modulated by altering the growth conditions in cell culture. We find that cultivation of AR42J cells in Panserin™ 401, a serum-free medium, enhances the induction of granule formation in the presence or absence of dexamethasone when compared to standard conditions including serum. Biochemical and morphological studies revealed an increase in ZG markers on the mRNA and protein level, as well as in granule size compared to standard conditions. Our data indicate that this effect is related to pronounced differentiation of AR42J cells. To address if enhanced expression of ZG proteins promotes granule formation, we expressed several zymogens and ZG membrane proteins in unstimulated AR42J cells and in constitutively secreting COS-7 cells. Neither single expression nor co-expression was sufficient to initiate granule formation in AR42J cells or the formation of granule-like structures in COS-7 cells as described for neuroendocrine cargo proteins. The importance of our findings for granule formation in exocrine cells is discussed.
Available online 5June 2012
Gesehen am 27.06.2018